Estonia: Making the Most of Globalisation - Price, Robert (OECD Economics Department Working Papers, 2011)
Estonia has already experienced many benefits of increasing international integration, most obviously in significant convergence. From the Russian crisis in 1998 to the great recession in 2009 Estonia gained an impressive 20% in GDP per capita relative to the EU27 average in PPPs. Like the other Baltic economies, however, a considerable part of earlier convergence gains was lost in the crisis, the impact of which was aggravated by the collapse of world trade. While this was also true for Ireland, central European countries in the process of catching up, like Czech Republic, Poland and Slovakia, have been less affected by the crisis and have been able to maintain most of their convergence gains. Moreover, prior to the recession Estonia's gap in income and productivity levels compared with the EU average was still around 30% and as the country emerges from recession it faces major policy challenges to regain its pre-crisis rate of growth potential. A greater focus on closing the productivity gap in the manufacturing-for-export sector compared with other transition countries would serve as a useful and challenging benchmark in order to get more out of globalisation